High-resolution fleezers reveal duplex opening and stepwise assembly by an oligomer of the DEAD-box helicase Ded1p - Eric M. Patrick; Rajeev Yadav; Kasun Senanayake; Kyle Cotter; Andrea A. Putnam; Eckhard Jankowsky; Matthew J. Comstock (Nature Communications)
Abstract DEAD-box RNA-dependent ATPases are ubiquitous in all domains of life where they bind and remodel RNA and RNA-protein complexes. DEAD-box ATPases with helicase activity unwind RNA duplexes by local opening of helical regions without directional movement through the duplexes and some of these enzymes, including Ded1p from Saccharomyces cerevisiae, oligomerize to effectively unwind RNA duplexes. Whether and how DEAD-box helicases coordinate oligomerization and unwinding is not known and it is unclear how many base pairs are actively opened. Using high-resolution optical tweezers and fluorescence, we reveal a highly dynamic and stochastic process of multiple Ded1p protomers assembling on and unwinding an RNA duplex. One Ded1p protomer binds to a duplex-adjacent ssRNA tail and promotes binding and subsequent unwinding of the duplex by additional Ded1p protomers in 4–6 bp steps. The data also reveal rapid duplex unwinding and rezipping linked with binding and dissociation of individual protomers and coordinated with the ATP hydrolysis cycle.